PENGARUH PERUBAHAN VOLUME CYLINDER HEAD DAN TINGGI LUBANG EXHAUST TERHADAP KENAIKAN DAYA PADA SEPEDA MOTOR F1ZR - -, Sudarsono (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2005)
The aim of this research is to know the effect of the change of cylinder head and the height of exhaust port to obtain great and safe power. Cylinder has many ports which are used in scavenging process (proses pemasukan, pembilasan dan proses pem-buangan) Exhaust port determines compression that is occurred in two stroke engine cycle and influences the engine characters. In standard condition, revolution 1500 produced 2 Nm torque. After modification, torque decreased to 1,5 (Nm). New torque increased in revolution 2000 rpm with 3,1 (Nm). Torque reached a peak from 10,8 (Nm) in revolution 8500 rpm to 13,6 (Nm) in revolution 10.000 rpm. Power produced in standard condition was 0,4 (Hp) in revolution 1500 rpm. After modification, it decreased to 0,3 (Hp). New power increased in revolution 3500 rpm. Power reached a peak from 12,9 (Hp) in revolution 8500 rpm to 19 (Hp) in revolution 10.000 rpm.